Comparative Analysis of Early Postoperative Cognitive Decline Following Isoflurane versus Sevoflurane Anesthesia in Geriatric Patients: A Prospective Observational Study - Recky Antoni; Nopian Hidayat; Dino Irawan (HM Publisher, 2026)
Background: As the global geriatric population expands, postoperative cognitive dysfunction (POCD) has emerged as a critical perioperative complication. While volatile anesthetics are standard for maintenance, conflicting evidence exists regarding the comparative neurotoxicity of Isoflurane and Sevoflurane, particularly in resource-limited settings where cost influences agent choice. This study aimed to evaluate and compare the magnitude of early cognitive decline associated with these two agents in an Indonesian geriatric cohort. Methods: We conducted a prospective comparative observational study involving 40 geriatric patients (aged ≥60 years, ASA II-III) undergoing elective non-cardiac surgery at Arifin Achmad Regional General Hospital, Indonesia. Patients were recruited via consecutive sampling and allocated to receive maintenance anesthesia with either Sevoflurane (n=20) or Isoflurane (n=20) according to standard clinical protocols. Cognitive function was assessed preoperatively and at 72 hours postoperatively using the Montreal Cognitive Assessment-Indonesian Version (MoCA-INA). The primary outcome was the magnitude of cognitive change (Delta score) and the incidence of cognitive decline. Results: Baseline characteristics were homogenous (p > 0.05). The Sevoflurane group exhibited a non-significant trend toward decline (Pre: 26.85 ± 1.09 vs. Post: 26.45 ± 1.28; p = 0.057) with a mean delta of 0.40. Conversely, the Isoflurane group demonstrated a statistically significant deterioration (Pre: 26.90 ± 1.07 vs. Post: 25.90 ± 1.55; p = 0.008) with a mean delta of 1.00. The magnitude of decline was significantly greater in the Isoflurane group (p = 0.026). The incidence of early cognitive decline was 25% for Isoflurane versus 10% for Sevoflurane. Conclusion: Isoflurane anesthesia is associated with a greater magnitude of early postoperative cognitive decline compared to Sevoflurane in geriatric patients. While Sevoflurane is not devoid of cognitive impact, it appears to offer a superior safety profile for early neurocognitive recovery. These findings suggest Sevoflurane may be the preferable agent for geriatric anesthesia in settings where newer agents like Desflurane are unavailable.